Right to Education for Irregular Migrant Children in Malaysia; A Comparative Analysis - Maheran, Makhtar; Khairun-Nisaa, Asari; Mohd Lotpi, Mohd Yusob (2015)
Irregular migrants are defined as persons who enter into a particular country through illegal means or persons who had lawfully entered into the country but overstayed after the expiry of their permits. Irregular migrant children are children who are born from these irregular migrant parents. Irregular migrants do not have the right to stay in the country and thus they are subjected to detainment and deportation to their home country according to the law of immigration. This process usually takes time and during this period, many of their children’s basic rights may be refused or denied, such as the right to education and the right to health care. In Malaysia, the law does not guarantee the right to education for irregular migrant children and thus, they would continuously be denied of this right so long as they remain in Malaysia illegally. This would significantly affect their intellectual development which is vital for preparation of adulthood. Hence, the paper seeks to examine the legal aspects of the right to education for irregular migrant children under the Malaysian laws and under the International law and to compare that with the laws of United Kingdom.